2015
DOI: 10.1080/0969594x.2015.1066307
|View full text |Cite
|
Sign up to set email alerts
|

Educational effectiveness in Chilean secondary education: comparing different ‘value added’ approaches to evaluate schools

Abstract: This article reports an original investigation into school performance measures and the multilevel nature of pupil achievement data in the Chilean school system using a sample of 177,461 students, nested within

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Previous studies on school effects in Chile using raw cross-sectional data have estimated a between-school variance ranging from 30 to 50% (e.g., Mizala, Romaguera, & Ostoic, 2004;OECD, 2013;Willms & Somers, 2001). When applying contextualised value-added models, school effects are found to be in the order of 6 to 20% (Muñoz-Chereau & Thomas, 2016, Troncoso et al, 2016.…”
Section: It Follows That the Magnitude Of School Effects On Student Amentioning
confidence: 94%
“…Previous studies on school effects in Chile using raw cross-sectional data have estimated a between-school variance ranging from 30 to 50% (e.g., Mizala, Romaguera, & Ostoic, 2004;OECD, 2013;Willms & Somers, 2001). When applying contextualised value-added models, school effects are found to be in the order of 6 to 20% (Muñoz-Chereau & Thomas, 2016, Troncoso et al, 2016.…”
Section: It Follows That the Magnitude Of School Effects On Student Amentioning
confidence: 94%
“…Muñoz-Chereau (2018) found that the percentage of total variance in student's math Raw attainment attributable to differences between primary schools reduced from 28.5% to 14.5% after controlling for aspects arguably out of the school control, indicating that the pupil intake and contextual features of Chilean primary schools exert a powerful influence on students' outcomes. Without VAM, these differences might be wrongly attributable to differences between schools' effectiveness, when in reality they are by large due to prior attainment and socioeconomic inequalities (Manzi, San Martín & Van Bellegem, 2011;Muñoz-Chereau, 2013;Muñoz-Chereau & Thomas, 2016;Torres, 2018).…”
Section: The Context: Chilean New Accountability Systemmentioning
confidence: 99%
“…achievement and progress, demonstrated by statistically significant differences between schools in relation to pupils' value added progress. Whilst raw measures of pupils' academic outcomes are useful for highlighting the attainment gaps at the school system, it is typically considered a poor indicator for other purposes -such as school accountability, school improvement or school choice-because making the school solely responsible for the results of their students, without accounting for external factors, is not fair, nor defendable (Muñoz-Chereau & Thomas, 2016).…”
mentioning
confidence: 99%
“…Although in primary education, there seems to be no difference between boys' and girls' results [24], in secondary education, girls tend to perform worse in mathematics and better in reading and writing [13,25]. This could be explained by the influence of gender stereotypes still present in today's society [26].…”
Section: Introductionmentioning
confidence: 99%